Pastoralism: Animal health and food safety situation analysis, Kenya and Tanzania - Wakhungu, Judi W.; Wesongah, J.; Galgalo, T.; Msalya, G.; Grace, Delia; Unger, Fred; Alonso, Silvia (International Livestock Research Institute, 2014)
Pastoralism is a farming system in societies that derive majority of their food and income from livestock production. This form of farming system is practised in the world’s arid and semi arid lands (ASALs). It is estimated that 70% of the landmass in the Horn of Africa is dry land; in Kenya 80% of the landmass is classified as ASAL while approximately half of Tanzania consists of dry land. These dry lands can only be effectively utilised when used for livestock rearing, supporting wildlife resource harvesting and tourism. In this paper we present a current situation analysis of animal health and its implication on food safety based on primary data collected from pastoralists in Kajiado County, Kenya and in Tanga and Morogoro regions in Tanzania. Less than 10% of pastoralists in these communities engage in crop farming to supplement household income, and with their high dependency on livestock rearing, animal health challenges are a significant problem. We report on the livestock diseases with high prevalence and postulate their effects on food safety and food security in pastoral communities. We also explore the extent of species rearing diversification, pastoralist trade orientation, and practices that may expose the community and their trading partners to animal and zoonotic infections. We also assess access to animal health service providers within these pastoral areas and veterinary drug usage that may have significant implications on animal health and food safety.